125k views
4 votes
The screenshot below...

The screenshot below...-example-1

1 Answer

4 votes

For this case we have:

Expression 1:


\frac {2m ^ 2-4m} {2 (m-2)} = \frac {2m (m-2)} {2 (m-2)} = m

Expression 2:


\frac {m ^ 2-2m + 1} {(m-1)} = \frac {(m-1) (m-1)} {(m-1)} = (m-1)

Expression 3:


\frac {m ^ 2-3m + 2} {m ^ 2-m} = \frac {(m-2) (m-1)} {m (m-1)} = \frac {(m-2) } {m}

Expression 4:


\frac {m ^ 2-m-2} {m ^ 2-1} = \frac {(m-2) (m + 1)} {(m + 1) (m-1)} = \frac {( m-2)} {(m-1)}

Answer:

1.D

2.B

3.A

4.C

User Alex Reisner
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.